Memahami Hubungan Agama Dan Masyarakat, Iman Dalam Pengaruh Media Sosial (International Forum of Researchers and Lecturers, 2024)
Society in the historical strata has had a fairly close relationship with religion since prehistoric times. For society, religion is seen as the beliefs and behaviors that society uses to address important problems that cannot be solved by the technical systems and organizational techniques for which it is known. To overcome this limitation, humans use the manipulation of supernatural powers. The notion of